Leadership and national security: an interrogation of the Boko Haram violence in Nigeria. Issue 1 (2nd January 2017) - Fasakin, Akinbode
ABSTRACT: This study contends that an analysis of the nexus between leadership and security offers useful insights into explaining conflict by stating that the conceptualisation of these argots, especially through the definition of leadership as a process, helps to explain and address Nigeria's security challenges. By arguing that leaders' ability to establish mutuality with their followers in any situation and set collectively-generated means for attaining these set goals for societal security, the study shows how such a relationship creates a secured state. This is not the case in Nigeria, where leaders' security decisions are influenced by external actors rather than by their followers. By showing that the Nigerian ruling elite's security agendas intersect with dominant global notions of security while neglecting genuine security interests of ordinary Nigerians, the study contextualises the complex global and local security interests in Nigeria. The lack of an intersection at home, however, has contributed to the emergence of extremists such as the Boko Haram sect, as well as the escalation of the acts of violence they perpetrate. As national insecurities become complex and intractable, 'elegant' or unilinear solutions – such as a military approach – lack the capacity to address these problems.